2002
DOI: 10.1093/jxb/erf065
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of leaf nitrogen and photosynthetic capacity within the foliage of individual trees: disentangling the effects of local light quality, leaf irradiance, and transpiration

Abstract: There is presently no consensus about the factor(s) driving photosynthetic acclimation and the intra-canopy distribution of leaf characteristics under natural conditions. The impact was tested of local (i) light quality (red/far red ratio), (ii) leaf irradiance (PPFD(i)), and (iii) transpiration rate (E) on total non-structural carbohydrates per leaf area (TNC(a)), TNC-free leaf mass-to-area ratio (LMA), total leaf nitrogen per leaf area (N(a)), photosynthetic capacity (maximum carboxylation rate and light-sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 53 publications
6
45
0
1
Order By: Relevance
“…Changes in the relationship between SLN and PPFD have been related to plant size and N status (Lötscher et al, 2003). There is also some evidence that light quality (in particular the red to far-red ratio) influences N distribution in the canopy (Rousseaux et al, 1999;Frak et al, 2002), but the spectral component of the light gradient is probably less important than the total irradiance component (Pons and de Jong-van Berkel, 2004). It has clearly been demonstrated that accumulation of cytokinins imported through the xylem is involved in the regulation of vertical leaf N distribution (Pons et al, 2001;Boonman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the relationship between SLN and PPFD have been related to plant size and N status (Lötscher et al, 2003). There is also some evidence that light quality (in particular the red to far-red ratio) influences N distribution in the canopy (Rousseaux et al, 1999;Frak et al, 2002), but the spectral component of the light gradient is probably less important than the total irradiance component (Pons and de Jong-van Berkel, 2004). It has clearly been demonstrated that accumulation of cytokinins imported through the xylem is involved in the regulation of vertical leaf N distribution (Pons et al, 2001;Boonman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that in some plant species FR-E light causes reductions in photosynthetic capacity, CO 2 assimilation and nitrogen levels (Frak et al 2002;Boccalandro et al 2009;Cagnola et al 2012). We investigated this in soybean by measuring levels of C and N in shoots and roots and compared the impact of TMX on C and N levels under FR-D and FR-E light.…”
Section: Tmx Does Not Prevent Reduction In C/n Under Fr-e Lightmentioning
confidence: 99%
“…Light intensity and quality change quickly within natural canopies at different time scales exposing single leaf elements to a variable stream of photons (Frak et al 2002;Yamashita et al 2002). Dynamic acclimation of photosynthetic efficiency to these changes in environmental light conditions are still not well understood (Rascher and Nedbal 2006) and novel approaches to measure canopy structure and function simultaneously are urgently needed.…”
Section: Mapping Of Structure and Function Of Natural Canopies By Hypmentioning
confidence: 99%